2021
DOI: 10.1155/2021/4352910
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study on Hydrate Production Using a Slow, Multistage Depressurization Strategy

Abstract: Optimization of the depressurization pathways plays a crucial role in avoiding potential geohazards while increasing hydrate production efficiency. In this study, methane hydrate was formed in a flexible plastic vessel and then gas production processes were conducted at constant confining pressure and constant confining temperature. The CMG-STARS simulator was applied to match the experimental gas production behavior and to derive the hydrate intrinsic dissociation constant. Secondly, fluid production behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The simulator considers the coupling effect of fluid flow, heat transfer, and fines transport in porous media and wellbore. 58…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The simulator considers the coupling effect of fluid flow, heat transfer, and fines transport in porous media and wellbore. 58…”
Section: Parametermentioning
confidence: 99%
“…The CMG‐STARS is primarily developed for thermal recovery. The simulator considers the coupling effect of fluid flow, heat transfer, and fines transport in porous media and wellbore 58 . Many scholars use this software to simulate hydrate.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…This causes the decomposition of hydrate to slow down and reduces the exploitation rate. The main purpose of the laboratory to simulate the decompression of hydrate production is to optimize the rate and range of decompression. , In addition, other methods can be combined to increase the gas production rate and recovery efficiency. The following mainly describes the development of the reactor used in the laboratory simulation exploitation experiment, the comparison of the gas recovery efficiency, and various parameters of the main reduced pressure exploitation scheme on reactors of different scales.…”
Section: Reactors For Fundamental Studies On Gas Hydratementioning
confidence: 99%
“…The results showed that stepwise depressurization could obtain a more stable gas production rate but would prolong the decomposition time of hydrate. Li et al 35 studied the gas production behavior of hydrate reservoirs under different depressurization paths by combining experiment and simulation. The results show that the slow stepwise depressurization strategy is helpful to improve the gas−water ratio and avoid the sharp temperature drop in the reservoir.…”
Section: Introductionmentioning
confidence: 99%